Evaluasi Faktor Lingkungan dan Biaya Tenaga Kerja terhadap Efektivitas Operasional di Café D’Empire Cikarang - Gusti Muhammad Yngwei Rayhan Syah; Sutrisno; Agustian Suseno; Vikri Al Fauzan; Panca Paripurna (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research was conducted to analyze the influence of work environment and compensation on employee performance at Café D’Empire Cikarang. The background of this study is based on the importance of employee roles in supporting the operational success of companies, particularly in the competitive food and beverage service industry. This study uses a quantitative method with a multiple linear regression approach, and data were collected through questionnaires distributed to all employees of Café D’Empire Cikarang. Data analysis was carried out using SPSS software through a series of tests including validity, reliability, classical assumption tests, F-test, and t-test. The results of this study indicate that work motivation, work environment, job training, and compensation at Café D’Empire Cikarang simultaneously have a significant influence on employee performance, contributing 19.2% to the performance variable, while the remaining 81.8% is influenced by other variables not examined in this study.